GAS FIELD DEVELOPMENT ALTERNATIVES EVALUATION USING REAL OPTIONS - CASE IN PRODUCTION SHARING CONTRACT IN INDONESIA - ILHAM RATMAN (NIM 29115525), DONY
Oil and gas exploitation is an example of industry exposed to capital intensive investment with many inherent risk factors and high uncertainty. Increased volatility of oil price in recent years and the shift of oil and gas field to frontier location such in offshore deep water has made it more important for investment decision shall reflect understanding all risks to economic value under all possible scenarios. Discounted Cash Flow (DCF) analysis as the most common method of valuation used in capital budgeting performed under rigid assumptions which often underestimate or ignore the extent of uncertainty and flexibility in the project alternatives. Other method such as Real Options has been introduced to complement DCF to acknowledge the value of uncertainty and flexibility in the project economic evaluation to sufficiently provide references for investment decision making process. This study utilizes DCF and Real Options approach for economic valuation analysis implemented in the real investment opportunity of offshore deep water natural gas field in Indonesia under production sharing contract fiscal term with the purpose to extent the degree of evaluation which acknowledge the presence of uncertainties and flexibilities in the project development alternatives. Analysis conducted using quantitative modelling and simulation utilize Monte Carlo and Real Options binomial method. Primary data uses Company reserves and costs estimation of initial alternative and supported with market data and interview with subject matter experts within project team. Initially, under static DCF approach, analysis suggested that no other alternatives more compelling than initial alternative of built new FPU (Floating Production Unit). However, by incorporating managerial flexibility and uncertainties using Real Options, the results advise different alternative to be pursued under different considered scenarios. Overall, the result of project valuation provide more understanding the impact of risk factor and flexibility to project profitability. Analysis results also indicate that approval of production period extension is crucial factor to overall profitability of the project. Real Options analysis structure implemented in this study is potential to be implemented for other project and combine with sensitivity and scenario analysis to improve project decision making process.